Biological parameters and population structure of Psammobatis extenta in Ubatuba region, north coast of the State of São Paulo, Brazil - Martins, I. A.; Martins, Cyntia Ludovico [UNESP]; Leme, AHA (Cambridge University Press, 2005)
Specimens of the zipper sand skate Psammobatis extenta were collected in the region of Ubatuba off the northern coast of the State of São Paulo, Brazil, monthly for once year (January - December 2000), at 25- to 40-m isobaths. A total of 123 individuals were caught. The total length (TL) of females averaged 224.6 mm, and of males 217 mm. The overall sex ratio was 1:1. Analysis of the length-weight relationship indicated the existence of positive allometry in females, and isometry in males. The length at onset of sexual maturity was determined for both sexes; females reached sexual maturity at smaller sizes than males (TL50 = 230.7 and TL50 = 237.7 mm respectively). Females showed functional parity of both ovaries and uteri. Females that were pregnant or were carrying vitellogenic oocytes were observed during nine of 12 months of the survey, indicating a continuous reproductive cycle. Psammobatis extenta was most abundant from January to April, and again from June to October. Most individuals were collected at the 40-m isobath. Both adults and neonates were collected in the study area. However, adolescent skates were scarce, which either indicates differential occupation of the area, or suggests that the shallow waters of the continental shelf are used as breeding grounds.